Analysis of drug resistance and mutation profiles in Mycobacterium tuberculosis isolates in a surveillance site in Beijing, China. Issue 1 (January 2021) - Zhang, Jie; Ren, Yixuan; Pan, Liping; Yi, Junli; Guan, Tong; Yang, Xinyu; Zhang, Zongde
Objective: This study analyzed drug resistance and mutations profiles in Mycobacterium tuberculosis isolates in a surveillance site in Huairou District, Beijing, China. Methods: The proportion method was used to assess drug resistance profiles for four first-line and seven second-line anti-tuberculosis (TB) drugs. Molecular line probe assays were used for the rapid detection of resistance to rifampicin (RIF) and isoniazid (INH). Results: Among 235 strains of M. tuberculosis, 79 (33.6%) isolates were resistant to one or more drugs. The isolates included 18 monoresistant (7.7%), 19 polyresistant (8.1%), 28 RIF-resistant (11.9%), 24 multidrug-resistant (MDR) (10.2%), 7 pre-extensively drug-resistant (XDR, 3.0%), and 2 XDR strains (0.9%). A higher rate of MDR-TB was detected among previously treated patients than among patients with newly diagnosed TB (34.5% vs. 6.8%). The majority (62.5%) of RIF-resistant isolates exhibited a mutation at S531L in the DNA-dependent RNA polymerase gene. Meanwhile, 62.9% of INH-resistant isolates carried a mutation at S315T1 in the katG gene. Conclusion: Our results confirmed the high rate of drug-resistant TB, especially MDR-TB, in Huairou District, Beijing, China. Therefore, detailed drug testing is crucial in the evaluation of MDR-TB treatment.